The hemoglobins of the sub-Antarctic fish Cottoperca gobio, a phyletically basal species. Oxygen-binding equilibria, kinetics and molecular dynamics - D. Giordano; L. Grassi; J. Friedman; D. Dankster; U. Samuni; G. di Prisco; C. Verde; VERGARA, ALESSANDRO; MAZZARELLA, LELIO (FEBS Journal, 2009)
The dominant perciform suborder Notothenioidei is an excellent study group for assessing the evolution and functional importance of biochemical adaptations to temperature. The availability of notothenioid taxa in a wide range of latitudes (Antarctic and non-Antarctic) provides a tool to enable identification of physiological and biochemical characteristics gained and lost during evolutionary history. Non-Antarctic notothenioids belonging to the most basal families are a crucial source for understanding the evolution of hemoglobin in high-Antarctic cold-adapted fish. This paper focuses on the structure, function and evolution of the oxygen-transport system of Cottoperca gobio, a sub-Antarctic notothenioid fish of the family Bovichtidae, probably derived from ancestral species that evolved in the Antarctic region and later migrated to lower latitudes. Unlike most high-Antarctic notothenioids, but similar to many other acanthomorph teleosts, C. gobio has two major hemoglobins having the b chain in common. The oxygenbinding equilibria and kinetics of the two hemoglobins have been measured. Hb1 and Hb2 show strong modulation of oxygen-binding equilibria and kinetics by heterotropic effectors, with marked Bohr and Root effects. In Hb1 and Hb2, oxygen affinity and subunit cooperativity are slightly higher than in most high-Antarctic notothenioid hemoglobins. Hb1 and Hb2 show similar rebinding rates, but also show significant dynamic differences that are likely to have functional consequences. Molecular dynamic simulations of C. gobio Hb1 were performed on the dimeric protein in order to obtain a better understanding of the molecular basis of structure ⁄ function relationships.